Experimental study on degree of match between slurry and ground based on particle retention rate. (October 2021) - Lin, Yufeng; Fang, Yong; He, Chuan; Wang, Wei
Highlights: An optimal apparatus for slurry infiltration tests with grooved sidewall is proposed. The concept of primary and secondary filter cake is proposed. A new method to evaluate the degree of the match between the slurry and the ground based on particle retention rate λ is proposed. Considering the clogging and filtering behavior, a new understanding of the filter cake and infiltration zone is proposed. Abstract: Slurry support, which is established by slurry infiltration, is essential to drilling with a slurry shield. In highly permeable soils, the slurry penetrates the ground and the required support force cannot be built up. Hence, large particles are usually added to the slurry to form filter cakes so that the slurry pressure can be applied on the excavation face successfully. In this paper, a series of penetration tests were carried out in which bentonite slurries with and without silt or sand were tested in different sandy grounds to investigate the influence of large particles on the slurry infiltration process. The commonly used apparatus was optimized structurally and operationally. The two distinct stages (i.e., mud spurt and filter cake formation) in the curves of discharged fluid in the penetration tests as well as the inflection point were analyzed. The elementary stable point, which is determined by the permeability of the filter cake, was proposed to identify the inflection point. Considering the clogging behavior of the slurry particles and the filtering ability of the ground, the particle retention rate ( λ ) was proposed to evaluate the degree of match between the slurry and the ground. The relationship between λ and the key index of the filter cake formation process was revealed. Based on the results of the tests in this paper, it is suggested to carry out infiltration tests and draw the curves (i.e., Ve - λ, Ts - λ, C - λ ) and then identify the degree of match between the slurry and the ground, rather than directly use the value provided in this paper to make the identification.